PENGARUH EKSTRAK SERAI (Andropogon nardus L.) TERHADAP KUNJUNGAN LALAT BUAH (Bactrocera dorsalis Hendel.) - Mardani, Roza; Jasmi, Jasmi; Zeswita, Armein Lusi (STKIP PGRI Sumbar, 2013)
ABSTRACTLemongrass is one of the favorite plants in Indonesia, which is often used by humans for cooking ingredients in addition to the lemon grass is also often used as ingredients of medicines . But the lemongrass plant has never been used as a vegetable fruit fly attractant material when compounds contained in the lemongrass was able to lure pests tanaman one methyl eugenol which is preferable by one insect Bactrocera dorsalis Hend . Based on the problems it has done research on the effect of lemongrass extract ( Andropogon nardus L. ) Fruit Fly Control Against Bactrocera dorsalis Hend . This research was conducted in the Laboratory of Zoology STKIP PGRI Padang West Sumatra in July-August , 2013, this study used a completely randomized design ( CRD ) with 4 treatments and 6 replicates of each concentration was 1 ml , 2 ml , 3 ml , 4 ml . From the research that has been carried out showed that the extract of lemongrass attractant effect on fruit fly Bactrocera dorsalis . On the activity of the flies the fastest time to reach the fruit fly extracts is on IV treatment while the longest time in treatment I. Analysis of variance results showed that there is a difference in treatment between the F count > F table which means treatment significantly affect fruit fly attractant Bactrocera dorsalis Hend.Â Â